2018
DOI: 10.5751/ace-01265-130209
|View full text |Cite
|
Sign up to set email alerts
|

Who's “hooting”? Motivations and scientific attitudes of Manitoban citizen science owl surveyors

Abstract: Wildlife and Fisheries Branch, Manitoba Sustainable Development, 3 Discover Owls ABSTRACT. Citizen science is gaining popularity as a means for all persons to participate in and contribute to scientific projects, and can increase our understanding of avian conservation and ecology by facilitating the collection of more data. Understanding the type of person who participates in citizen science projects, including their motivations, behaviors, and gains, allows researchers to better recruit and retain participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The limited number of citizen science studies that have attempted to examine motivations of different groups of people have also focussed primarily on variation in motivations by age, finding again that younger participants are more likely to be motivated by Egoism motivations such as the potential to enhance their career or reputation (Alender 2016;Ng, Duncan, and Koper 2018), to learn new things (Asingizwe et al 2020), to have fun (Brouwer and Hessels 2019), and to learn about nature (Ganzevoort et al 2017), whereas older participants are more likely to have Values motivations such as wanting to contribute to science and to nature conservation (Ganzevoort et al 2017). A small number of studies have looked at other characteristics and have found that education level (Brouwer and Hessels 2019) and gender have some influence on motivations for participation (Jones et al 2018), whereas others have not found any association between demographic characteristics and motivations (Richter et al 2018).…”
Section: Variations In Motivations Between Demographic Groupsmentioning
confidence: 99%
“…The limited number of citizen science studies that have attempted to examine motivations of different groups of people have also focussed primarily on variation in motivations by age, finding again that younger participants are more likely to be motivated by Egoism motivations such as the potential to enhance their career or reputation (Alender 2016;Ng, Duncan, and Koper 2018), to learn new things (Asingizwe et al 2020), to have fun (Brouwer and Hessels 2019), and to learn about nature (Ganzevoort et al 2017), whereas older participants are more likely to have Values motivations such as wanting to contribute to science and to nature conservation (Ganzevoort et al 2017). A small number of studies have looked at other characteristics and have found that education level (Brouwer and Hessels 2019) and gender have some influence on motivations for participation (Jones et al 2018), whereas others have not found any association between demographic characteristics and motivations (Richter et al 2018).…”
Section: Variations In Motivations Between Demographic Groupsmentioning
confidence: 99%
“…As shown in Figure 2b, there were no issues preventing participants from contributing to a CS initiative due to their gender, as both males and females were found to participate in the vast majority (97%) of CS initiatives. For example, a questionnaire developed to retrieve information regarding the motivations and scientific attitudes from past participants of the Manitoba Nocturnal Owl Survey revealed that "Respondents were fairly evenly split by gender" [57] (para. 15).…”
Section: Exclusion and Inclusion Demographic Factorsmentioning
confidence: 99%
“…"Interpersonal interactions and contributions to a conservation project were each described by 22% of respondents, followed by general enjoyment or "fun" (17%)" [57] (p. 5).…”
Section: %mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, having the opportunity to be in nature was identified as a critical factor for participation in a Canadian community science program (Ng et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%